A Feminist Discourse Analysis of Writer's Gender Biases about Violence Against Women (Journal of the College of Languages (JCL), 2021)
The present study is concerned with the writer's ideologies towards violence against women. The study focuses on analyzing violence against women in English novel to see the extent the writers are being affected and influenced by their genders. It also focuses on showing to what extent the writer's ideologies are reflected in their works. Gender influences social groups ideologies; therefore, when a writer discusses an issue that concerns the other gender, they will be either subjective or objective depending on the degree of influence, i.e., gender has influenced their thoughts as well as behaviors. A single fact may be presented differently by different writers depending on the range of affectedness by ideologies. The study aims to uncover the hidden gender-based ideologies by analyzing the discursive structure of a novel based on Van Dijk's model (2000) of ideology and racism. The selected novel is based on discussing violence against women. The study will later on reveal the real writer’s gender-based ideologies and whether the writer is a feminist or an anti-feminist? Or Is he prejudiced? Or Is he biased?